Faktor Risiko Kejadian Demam Berdarah Dengue di Wilayah Kerja Puskesmas Cibinong Tahun 2025 - Silva Fadila Rahmah; Rony Darmawansyah Alnur (Universitas Pahlawan Tuanku Tambusai, 2025)
One of the public health problems in Indonesia is Dengue Fever (DF) caused by the dengue virus transmitted through the bite of the Aedes aegypti mosquito. A study conducted in the working area of the Cibinong Health Center, Bogor Regency, in 2025 aimed to determine the relationship between environmental factors and community behavior with the incidence of Dengue Fever (DF). Using a case-control design with a sample of 103 cases and 103 controls selected by simple random sampling, primary data were collected through interviews, observations, and questionnaires, as well as secondary data from the medical records of the Health Center. Bivariate analysis using the Chi-Square test showed no significant relationship between container cleaning, presence of larvae, occupancy density, habit of hanging clothes, storing used goods, storing uncovered water, knowledge, and attitudes with the incidence of DF (p>0.05). These results indicate that the environmental factors and community behaviors studied did not play a significant role in the occurrence of DF in the area. In conclusion, most of the community in the working area of the Cibinong Health Center have carried out dengue prevention efforts well, so the risk factors studied did not significantly influence the increase in DF cases in 2025